#TITLE_ALTERNATIVE# - ADHITIA PUTRA (NIM: 15109093); Pembimbing: Dr. Heri Andreas, ST., MT.; Dr. Irwan Gumilar, ST., RIO
Nowadays, 3D modeling of a building has been growing rapidly. One of the ways to support the creation of 3D modeling is by using the TLS technology (Terrestrial Laser scanners). TLS can be utilized in various fields including: mapping, architecture, heritage, industry, construction, mining, police, and reverse engineering. The purpose of the final project is to produce a 3D modelof Al Irsyad Mosque Kota Baru Parahyangan and its size by using TLS technology.The stages to obtain 3D models by TLS include registration, meshing, and formation of the filter surface. This process uses local coordinates as reference. The making of surface mesh model is used by changing the shape of TIN (Triangulated Irregular Network) into a form surface. The final result of the research is a 3D model of the mosque. Based on the result, TLS can produce 3D model of mosque and its size, but the structure of the walls in the mosque are still not perfect due to lack of point clouds. The error of the 3D modeling is approximately 0,002 m. The error value is is generated after the registration process. The modelcan be used for documenting, archiving and referencing to help the reconstruction of mosque.